Enhancing Power Factor Performance of Capacitor Bank Systems through Control Circuit Reconfiguration - Yuli Prasetyo; Budi Triyono; Dimas Nur Prakoso; Santi Triwijaya; Muhammad Marco Dwi Yoga (International Journal of Engineering Continuity, 2026)
This study investigates a practical method to enhance the efficiency of a campus electrical distribution system by optimizing the control and power circuitry of a capacitor bank panel. The research addresses the persistent issue of low power factor and phase imbalance resulting from non-standard wiring configurations in existing installations. Unlike conventional maintenance procedures, the proposed rewiring strategy systematically redesigns the control and power connections to ensure accurate capacitor switching and reactive power compensation in accordance with operational load variations. A diagnostic improvement evaluation framework was employed, involving pre- and post-rewiring measurements of power factor, load current balance, and reactive power under both normal and full-load conditions. The rewiring intervention increased the power factor from 0.97 to 0.99 during normal operation and from 0.70 to 0.95 under full-load simulation (1100 kVA). These improvements corresponded to a measurable reduction in reactive power demand and overall system losses, indicating a substantial gain in energy efficiency and voltage stability. The findings confirm that targeted control circuit reconfiguration can significantly enhance the operational reliability of capacitor bank systems beyond conventional maintenance practices. This work contributes a replicable, technically validated approach for improving power quality in educational and industrial electrical installations.